Protecting children from nutritional and medical neglect in sub-Saharan Africa: a five-country study - Laird, Siobhan E. (Wiley, 2016)
This study focuses on the dominant definitions of nutritional and medical neglect used to identify child maltreatment. These originate from the United Kingdom and the United States, but are also utilised in the developing countries of the sub-Saharan region. Evidence adduced from secondary data gathered in five representative African countries seeks to demonstrate that the application of these dominant definitions of neglect is misleading in the socio-economic context which pertains in most of the sub-Saharan region. The statutes which domesticate the Convention on the Rights of the Child (CRC) in these African countries are examined to reveal some distinctive national variations in their child protection provisions. While predominantly reflecting Western definitions of neglect, some of the legal provisions embedded in African domestic laws offer insights into more functional concepts of child neglect. Notably some recognise a tension between deprivation which denies parents the resources to satisfactorily care for their child, and neglect whereby adequately resourced parents deny their child nourishment and medical assistance.